2021
DOI: 10.1186/s13019-021-01570-3
|View full text |Cite
|
Sign up to set email alerts
|

Right apical-posterior segmentectomy with abnormal anterior segmental bronchus and artery: a case report

Abstract: Background Displaced anterior segmental bronchus and pulmonary artery is extremely rare. A keen knowledge of such variations is required in the field of pulmonary segmentectomy, for unawareness of the structural variation could lead to intra- and postoperative complications. Case presentation A 50-year-old female presented to our department with suspected lung adenocarcinoma. Preoperative 3-dimensional computed tomographic bronchography and angiogr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Similarly, all the three translobar bronchi in this study were located in RUL. The B 2/2+3 that branched from B 4+5 within the fused HIF posed significant challenges in defining the boundary between RUL and RML during right upper lobectomy, because the HIFs were totally undeveloped in these patients ( 9 , 10 ). In this study, a new anomalous bronchial pattern was identified, namely common stem bronchus of RUL and RML.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, all the three translobar bronchi in this study were located in RUL. The B 2/2+3 that branched from B 4+5 within the fused HIF posed significant challenges in defining the boundary between RUL and RML during right upper lobectomy, because the HIFs were totally undeveloped in these patients ( 9 , 10 ). In this study, a new anomalous bronchial pattern was identified, namely common stem bronchus of RUL and RML.…”
Section: Discussionmentioning
confidence: 99%